An international examination of the economic effectiveness of banking recapitalization - Tahir, Suleiman; Adegbite, Emmanuel; Guney, Yilmaz (Elsevier, 2017)
While the literature on capital adequacy and bank recapitalization agrees on the importance of a minimum capital requirement, recurring financial crises across the world do little to suggest that capital adequacy is enough protection for banks, even when they fully comply. By examining the case of regulation compelled banking recapitalizations in a cross-country context (during the period 1990Q1–2016Q2), we scrutinize the effectiveness of banking recapitalization on the economies of recently recapitalized countries. We provide implications for international business research, practice and policy by highlighting the need for countries adopting the Basel capital adequacy framework to pay attention to the peculiarities of their economies, the supporting regulatory mechanisms and their comparative spare capacities.